La législature québécoise peut-elle implanter un système complet d'initiative et de référendum ? - Delwaide, Karl (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
In this article, the author asks himself whether it would be permissible for the Quebec Legislature to implement a full and complete initiative and referendum scheme, thereby giving to the people the means to enact their own laws. And the answer brought about is in the affirmative. The author reaches that conclusion, first, by looking at the concepts of sovereignty in the state, legislative supremacy and parliamentary sovereignty. The second step is related to the analysis of the power attributed to the Legislature to modify its own constitution. The author assumes that this large power of legislation coupled with the principle of legislative supremacy should be sufficient to make a court of justice sustain the constitutional validity of the legislative implementation of a complete initiative and referendum process. But some exceptions are made to that large and supreme legislative power. The « Office of Lieutenant Governor », the idea of making the Legislature the sole legislative organ in the state, the principles of representative democracy and responsible government, and the impossibility of binding the Legislature's future course of action are among the exceptions discussed in this article. Finally, the author urges the reader to take a new look at the case-law on the subject keeping in mind that traditonal values of government are not stuck in concrete: The B.N.A. Act, has it been recognized, has to keep up with today's reality. Direct democracy may be part of this reality.